Growth and Development of Children In Adolescent Mother In Gunungkidul - Dewi Rokhanawati; Rosmita Nuzuliana (International Journal of Health Science and Technology, 2021)
Adolescent mothers with poor knowledge and skills in parenting will adversely affect the development of children. In 2018, children under five in Gunung Kidul experienced developmental delays (1.05%). This study was descriptive observation with 30 respondents of adolescent mothers under 21 years of age. Questionnaires were used to complete the data. Other tools used were infantometer, weight scales, Denver II Form, Z Score table. The results show that predominant respondents have low education (66.7%) and the majority are housewives. The weight of the children is in accordance to their age, the majority of the height is normal, but 56.7% of children experience developmental delays